Civil Litigation in Education Contract Disputes in Islamic Boarding Schools: A Comparative Perspective on Thailand's Bromsgrove International School Model - Sari, Dewi Arnita; Hasbullah, Hasbullah; Saharudin, Saharudin; Islahuddin, Islahuddin (Faculty of Law, Universitas Pattimura, 2025)
Introduction: This study examines the effectiveness of civil litigation in resolving education contract disputes at the Watampone Blue Islamic Boarding School, South Sulawesi. As an educational institution based on Islamic values, Islamic boarding schools face legal challenges due to the lack of special regulations governing education contracts.Purposes of the Research: Evaluate the effectiveness of civil litigation in resolving education contract disputes at the Watampone Blue Islamic Boarding School. It aims to identify the causes of disputes, explore alternative resolution methods like mediation, and propose an updated framework for education contracts that integrates Sharia principles, legal protection, and clarity of rights and obligations in Islamic boarding schools.Methods of the Research: The research uses a qualitative approach with a case study method, through the analysis of contract documents and in-depth interviews with student guardians, pesantren managers, and legal practitioners.Results of the Research: Contract disputes in Islamic boarding schools stem from unequal bargaining, unclear clauses, and low legal awareness. While civil litigation is rarely used, mediation based on local wisdom is more common. The research calls for updating education contracts in these schools to integrate Sharia principles and ensure legal clarity and justice for all parties.